Sustained suppression of enterohepatic circulation of mycophenolic acid by antimicrobial‐associated diarrhea in a kidney transplant recipient with Crohn's disease: A case report - Ryota Tanaka; Asami Matsumoto; Ryosuke Tatsuta; Tadasuke Ando; Toshitaka Shin; Hiromitsu Mimata; Hiroki Itoh (Clinical Case Reports, 2022)
Abstract Mycophenolic acid (MPA) undergoes enterohepatic circulation. A kidney transplant patient on mycophenolate mofetil was treated with tazobactam/piperacillin for pyelonephritis, and developed antimicrobial‐associated diarrhea. Consequently, the MPA trough level decreased by approximately 90%. Furthermore, it took approximately a month for the MPA level to normalize even after diarrhea had resolved.